Structural change of lithium ion battery caused by repetitive charge and discharge / Seiichi Suzuki ... [et al.] - Suzuki, Seiichi; Katayama, Taiki; Tsunoda, Hiroyuki; Iwasaki, Toshiyuki; Ito, Takuya; Suganuma, Hideki; Kato, Shigeru; Kojima, Toshinori (Universiti Teknologi MARA, Pulau Pinang, 2015)
Lithium ion battery is one of the most promising technologies for electric power storage and soft energy path. However, inadequate handling of Lithium ion battery may cause spontaneous ignition. To reduce the risk of such accidents, changes of Lithium ion battery during repetitive charge and discharge cycles were investigated. By 400 cycles of charge and discharge, battery capability was reduced to about 80% of new one. After charge/discharge experiment, composition of organic materials in the electrolyte was analyzed by GC-FID. Gradual rise of diethyl fluorophosphate concentration in the electrolyte was observed. Surface structures of the electrodes were also investigated by SEM and XRD. XRD data of anode electrode also showed gradual decrease of diffraction angle. This suggests the increase of lattice constant during the deterioration process. Reflecting such structural change of molecular scale, morphological change of electrode surface was also observed. Surface grain of cathode electrode had more numbers of cracking with increasing cycle numbers. Image of cell volume change was captured by X-ray CT. Volume expansion of battery occurred in rectangular 006P type battery. These results may be caused by asymmetric dissociation and association of Lithium ion on the cathode surface.